Anti-reflux barrier competency can be estimated by gastric folds stretching during intragastric insufflation without special equipment - Tanaka, Hidenori; Inoue, Haruhiro; Shimamura, Yuto; Saino, Masachika; Ushikubo, Kei; Iwasaki, Miyuki; Yamamoto, Kazuki; Nishikawa, Yohei; Tanaka, Ippei; Tanabe, Mayo; Abiko, Satoshi; Boldbaatar, Gantuya; Onimaru, Manabu; Oka, Shiro (Endoscopy International Open, 2025)
Although the endoscopic pressure study integrated system (EPSIS) is useful to evaluate competency of lower esophageal sphincter as a major part of the anti-reflux barrier, its availability is limited. This study aimed to assess whether gastric fold stretching during insufflation can predict intragastric pressure (IGP) without special equipment.A retrospective analysis included 33 patients who underwent esophagogastroduodenoscopy and EPSIS between June and July 2024. Gastric fold stretching along the greater curvature at the level of the cardia, observed in a retroflex view during insufflation, was compared with EPSIS results by reviewing recorded videos. Time ranges were defined as follows, and IGP was measured at the end of each range: Time range 1, until the ratio of longitudinal fold thickness to the groove width between folds reached 1:2; Time range 2, until the ratio reached 1:4; and Time range 3, until the folds or mucosal ridges were almost flattened. Variability was assessed using the coefficient of variation (CV), calculated as the standard deviation divided by the mean.Time ranges 1, 2, and 3 were fully observed in 100%, 97%, and 70% of patients, respectively. Mean IGPs at the end of Time ranges 1, 2, and 3 were 8.9, 11.1, and 17.7 mmHg, with CVs of 0.32, 0.28, and 0.08, respectively.Flattening of gastric folds or mucosal ridges during insufflation is a reliable predictor of IGP. This finding may help identify patients with anti-reflux barrier dysfunction during regular endoscopic examination.
Keywords: Endoscopy Upper GI Tract; Reflux disease; Motility / achalasia; Diagnosis and imaging (inc. chromoendoscopy, NBI, iSCAN, FICE, CLE)